Improving Rotational Doppler Velocimetry Accuracy and Spectral Characteristics of Vortex Beam in Maritime Atmospheric Turbulence - Hongyang Wang; Zijing Zhang; Chengshuai Cui; Xinran Lv; Hao Yun; Hao Liu; Yuan Zhao (IEEE Photonics Journal, 2024)
The distortion of vortex beams in maritime atmospheric turbulence can significantly affect the precision of rotational velocity measurements and spectral characteristics; however, current research into this is limited. This study focused on the compensation capacity of the Gerchberg–Saxton (GS) phase recovery algorithm, which demonstrates a notable enhancement in metrics such as the optical field purity, rotational velocity measurement accuracy, signal-to-maximum sideband ratio of the distorted vortex beams. Simulation results indicate that the compensation for mode dispersion induced by the receiving aperture limitation in the remote transmission of long-wavelength beams leads to average purity improvements of up to 50.55%. The maximum beam waist radius corresponds to high purity (P > 0.7) increase from 0.56 to 1.01 cm. There is a stronger capacity for crucial metric improvements at the optimal beam waist radius. The performance degradation caused by aperture smoothing effects was effectively mitigated. The maximum improvement rates for purity and velocity measurement accuracy of the higher-order beams in remote transmission can reach 12.49-fold and 16.41%, respectively. Transmission distance emerged as a more crucial influencing factor for capacity enhancement than the orbital angular momentum (OAM) mode. This work provides an important theoretical support for improving the OAM purity and frequency characteristics of rotational velocimetry of vortex beams in maritime atmospheric turbulence.